Perovskite light emitting transistors - Cheng, Bryan Wei Hao (Nanyang Technological University, 2022)
Perovskite light-emitting transistors (PeLETs) are unique devices that combine two key functions of optoelectronics: electrical switching and amplification with light emission. They also provide a versatile platform for charge transport and recombination of charge carriers study in hybrid organic-inorganic perovskites; and are emerging materials with outstanding physical and chemical properties. Unfortunately, PeLETs suffer from low brightness and environmental instability related to intrinsic material limitations, such as temperature-activated trapping, ionic motion and polarization effects, which limit device performance and stability at ambient conditions.